Management of hypertension in the elderly with Defansi exercises - Diana Pefbrianti; Devi Hairina Lestari; M Noor Ifansyah (International Journal Of Community Service, 2024)
There are still many elderly who experience hypertension, if hypertension does not show symptoms the elderly rarely seek treatment, the elderly rarely do physical activity, Individuals who experience hypertension often experience complex problems such as pain, anxiety, and low family support. So that individuals experience limitations in carrying out activities and are still dependent on others around them. This community service is carried out in the village Tambak Baru ilir Martapura District, Banjar Regency City South Kalimantan. The measurement results obtained data that the elderly who experienced hypertention in pre hypertention and grade 1 hypertention as much as 31.4% and majority the age is on 45-54 years old as much as 45.7%. Defansi exercise is effective in overcoming hypertention in the elderly. Defansi exercises make blood vessels more relaxed, the body will become healthier and will also cause a gradual decrease in blood pressure.